Novel cyclometallated 5-π-delocalized donor-1, 3-di(2-pyridyl)benzene platinum(ii) complexes with good second-order nonlinear optical properties. Issue 1 (5th December 2018) - Fontani, Mattia; Garoni, Eleonora; Colombo, Alessia; Dragonetti, Claudia; Fantacci, Simona; Doucet, Henri; Soulé, Jean-François; Boixel, Julien; Guerchais, Véronique; Roberto, Dominique
Abstract : For platinum complexes bearing a cyclometallated 5-thiophene-1, 3-di(2-pyridyl)benzene, β EFISH increases following the order of the LUMO stabilization. Abstract : Five new platinum(ii ) complexes bearing a cyclometallated 5-π-delocalized donor-1, 3-di(2-pyridyl)benzene were prepared and fully characterized. Their second-order nonlinear optical (NLO) properties were determined by the Electric-Field Induced Second Harmonic generation (EFISH) technique, working in DMF solution with an incident wavelength of 1907 nm, whereas the dipole moments were determined by Density Functional Theory (DFT) calculations. Remarkably, the platinum(ii ) complex with a cyclometallated 5-guaiazulene-CHCH-1, 3-di(2-pyridyl)benzene appears as a very good candidate for application in photonics, being characterized by the largest second-order NLO response. Besides, it appeared that the nature of substituents on thiophene, chosen as π-delocalized moiety in position 5 of the 1, 3-di(2-pyridyl)benzene, strongly affects the NLO properties.